PENGARUH INFLASI, JAKARTA ISLAMIC INDEX, BAGI HASIL BANK SYARIAH TERHADAP INVESTASI REKSA DANA SYARIAH - Kurniawan, Elan (Kinerja, 2019)
The purpose of this study is to obtain empirical evidence about the problems discussed, namely "Influence of Inflation, Jakarta Islamic Index, and Profit-Sharing of Islamic Banks on Sharia Mutual Investment". Investment is proxied by the Net Asset Value of Sharia Funds. Presentation and analysis of research data in 2013-2017, using descriptive statistical analysis, panel data regression models, data estimation methods namely Chow Test, classical assumption analysis using normality test, multicollinearity test, and hypothesis testing. Based on the results of the analysis of this research data, positive inflation has a significant positive effect on Sharia Mutual Fund Investment, the Jakarta Islamic Index has a significant positive effect on Sharia Mutual Fund Investment, while Sharia Bank Profit Sharing is also significantly negative on Sharia Mutual Fund Investment.